2023
DOI: 10.7554/elife.83291
|View full text |Cite|
|
Sign up to set email alerts
|

Directed differentiation of human iPSCs to functional ovarian granulosa-like cells via transcription factor overexpression

Abstract: An in vitro model of human ovarian follicles would greatly benefit the study of female reproduction. Ovarian development requires the combination of germ cells and several types of somatic cells. Among these, granulosa cells play a key role in follicle formation and support for oogenesis. Whereas efficient protocols exist for generating human primordial germ cell-like cells (hPGCLCs) from human induced pluripotent stem cells (hiPSCs), a method of generating granulosa cells has been elusive. Here, we report tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 82 publications
(124 reference statements)
2
43
0
Order By: Relevance
“…We have previously demonstrated that hiPSC-derived OSCs are predominantly composed of granulosa-like cells and ovarian stroma-like cells. 21 In response to FSH hormonal stimulation in vitro , the OSCs produce growth factors and steroids necessary for paracrine interaction with oocytes and cumulus cells. 21 To investigate whether hiPSC-derived OSCs are functionally capable of promoting human oocyte maturation in vitro , as an approach to rescue immature denuded oocytes, we established a co-culture system of these cells with retrieved denuded immature oocytes and assessed maturation rates after 24-28 hours (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that hiPSC-derived OSCs are predominantly composed of granulosa-like cells and ovarian stroma-like cells. 21 In response to FSH hormonal stimulation in vitro , the OSCs produce growth factors and steroids necessary for paracrine interaction with oocytes and cumulus cells. 21 To investigate whether hiPSC-derived OSCs are functionally capable of promoting human oocyte maturation in vitro , as an approach to rescue immature denuded oocytes, we established a co-culture system of these cells with retrieved denuded immature oocytes and assessed maturation rates after 24-28 hours (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Human induced pluripotent stem cell (hiPSC) derived OSCs were created according to transcription factor (TF)-directed protocols described previously. 21 OSCs were produced in multiple batches and cryopreserved in vials of 120,000 to 150,000 cells each, and stored in the vapor phase of liquid nitrogen in CryoStor CS10 Cell Freezing Medium (StemCell Technologies).…”
Section: Preparation Of Ovarian Supporting Cells (Oscs)mentioning
confidence: 99%
See 1 more Smart Citation
“…OSCs were created from human induced pluripotent stem cells (hiPSCs) according to transcription factor (TF)-directed protocols described previously. 41 The OSCs were produced in multiple batches and cryopreserved in vials of 120,000 to 150,000 live cells each and stored in liquid nitrogen in CryoStor CS10 Cell Freezing Medium (StemCell Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work described the generation of ovarian support cells (OSCs) from human induced pluripotent stem cells (hiPSCS) in a rapid, efficient, and reproducible manner through transcription factor (TF)-directed differentiation. 41 The OSCs primarily are composed of FOXL2+ AMHR2+ granulosa-like cells as well as ovarian NR2F2+ stroma-like cells. The OSCs are steroidogenic, producing aromatase in response to follicle stimulating hormone (FSH) stimulation to catalyze the estradiol synthesis pathway, and produce the necessary growth factors needed for robust paracrine interaction with oocytes and cumulus cells.…”
Section: Introductionmentioning
confidence: 99%